Women and the Future of Mangrove in Meranti Island, Riau - Hesti Asriwandari; Rahmita Budiartiningsih; Desy Artina; Yusnarida Eka Nizmi; Yessi Yessi (International Journal of Agricultural Sciences, 2021)
Among the many preserved mangrove areas in Riau Province is the one located in the Meranti Islands Regency. However, the regency is prone to environmental pollution and destruction, so control efforts, namely prevention, management, and recovery, are needed to mitigate it. This study aims to explain women's involvement in the mangrove community's activities as well as their social position within said community. Their involvement will be able to explain their social position, whether they have the ability to make decisions on public activities or only act as objects of a patriarchal development process. This study uses a descriptive qualitative approach. The main informants in this study were women who were directly involved in the mangrove community activities, while the villagers who were not directly involved acted as supporting informants. The village women who were involved in the mangrove forest rehabilitation are all married, aged 29 to 50 years old, and have completed elementary school. Each woman has specialized activities, such as seeding, planting, and making dodol, syrup, and chips. Their role in the mangrove community has a great potential to control the balance between ecological and socio-economic benefits of mangrove forests. However, their activities are not independent. Their involvement is passive as it remains under the management of a coastal conservation leader, and it only serves to help their husbands because the rehabilitation of coastal areas will help maintain the habitat of fish and marine animals, which are their husbands' source of income.